Serum Levels of Inflammatory Cytokines in Helminth Infested Pregnant Women and Cord Blood of their Babies in Relation to Pregnancy Outcome (Nigerian Journal of Physiological Sciences, 2021)
Summary: Pregnancy places a very high demand on physical, physiological and immunological responses of females, especially when aggravated by parasitic infestation. There is strong evidence that maternal infestations with helminth have profound effects on immunity to helminths and other pathogens. This case-control study involved 245 pregnant women aged 18-40 years (>30 weeks of gestation) recruited from three secondary level hospitals in Ibadan, Nigeria. Morning stool samples collected from pregnant women were examine for intestinal helminths using formol-ether concentration method. A total of 38 participants comprising 17 Helminth Positive (HP) and 21 Helminth Negative (HN) pregnant women were purposely selected for the study. Sera from these women (38) and their babies’ cord (38) were analysed for immune factors [interleukins 6 and 8 (IL-6, IL-8), tumor necrosis factor-alpha (TNF-α) and immunoglobulin E (IgE)] were analyzed using ELISA. Anthropometric indices [weight and height in mothers and babies and Chest Circumference (CC) in babies] were measured using standard methods. Data were subjected to descriptive statistics and analysed using Student t-test and Pearson correlation at α0.05. Only Ascaris lumbricoides was found in the 17 (6.9%) infested pregnant women. The mean levels of IL-6 (57.8 ± 32.8 vs 52.8±39.6 pg/mL), IL-8 (24.3±3.5 vs 22.0±7.1 pg/mL) and IgE (333.3±96.6 vs 242.3±96.8 IU/mL) were similar in HP when compared with HN. In cord sera, IL-8 level was significantly higher in babies of HP (23.7±3.9 pg/mL) compared with babies of HN (20.1±5.9 pg/mL). The levels of IL-6, TNF-α and nutritional indices in HP had significant positive correlation with corresponding levels in babies of HP mothers. Only CC was significantly lowered in babies of HP compared with HN mothers. Other anthropometric indices were not significantly different. Therefore, this present study suggests that helminth infestation may lead to strong Th2 immune responses as is reflected by the cytokine levels of mothers and babies as well as anthropometric measurements of babies of infested mothers. The outcomes of this study provide basis to deworm pregnant women during pregnancy.